Constructing choice biographies: aspirational pathways and educational choices of young Roma migrants - Amalia Georgiana Sabiescu (Educazione Interculturale)
This article explores the dynamics between aspiration, formation and processes of educational and career choice among young Roma migrants in the United Kingdom, focusing on young people that are carving life and career pathways that diverge from traditional roles in their community. Drawing on empirical data from a research study on lifelong learning, the article theorises youth transitions through the sociology of youth concepts of normal biographies, where young people follow pre-established paths; and choice biographies, where new, often unprecedented roles are envisioned, such as being the first in the family to pursue higher education. The analysis highlights the transformative potential of aspirations in shaping the educational and professional trajectories of young Roma, while emphasising the crucial role of supportive family and social structures in calibrating these aspirations in response to the broader opportunity structure. The paper offers as well a critical appraisal of the conceptual utility of the distinction between normal and choice biographies, defining them as dual spaces of reflection encompassing purposeful decision-making and concrete steps toward the realisation of life projects.